2021
DOI: 10.21037/atm-21-1761
|View full text |Cite
|
Sign up to set email alerts
|

KCNQ1OT1 lncRNA affects the proliferation, apoptosis, and chemoresistance of small cell lung cancer cells via the JAK2/ STAT3 axis

Abstract: Background: Small cell lung cancer (SCLC) is a devastating and aggressive neuroendocrine carcinoma characterized by high cellular proliferation and early metastatic spread. Numerous studies have demonstrated that long noncoding RNAs (lncRNAs) can regulate tumor generation and development, including in SCLC.The current study aimed to assess the effect of the lncRNA, KCNQ1OT1, on the proliferation, apoptosis, and chemoresistance of SCLC and the potential underlying molecular mechanism.Methods: Matched chemo-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…In addition, KCNQ1OT1 has been reported to play a role in metabolic reprogramming in CRC. Chen et al demonstrated that KCNQ1OT1 modulates HCT116 and SW48 CRC cell proliferation in glucose metabolism reprogramming by stabilizing hexokinase 2 (HK2) [ 38 ]. Together, studies suggest that higher levels of KCNQ1OT1 in CRC patients could reduce the effectiveness of some chemotherapeutic regimens and may be useful as a predictive biomarker of drug response, a prognostic indicator, and an immune therapy target.…”
Section: Kcnq1ot1 In Human Cancersmentioning
confidence: 99%
“…In addition, KCNQ1OT1 has been reported to play a role in metabolic reprogramming in CRC. Chen et al demonstrated that KCNQ1OT1 modulates HCT116 and SW48 CRC cell proliferation in glucose metabolism reprogramming by stabilizing hexokinase 2 (HK2) [ 38 ]. Together, studies suggest that higher levels of KCNQ1OT1 in CRC patients could reduce the effectiveness of some chemotherapeutic regimens and may be useful as a predictive biomarker of drug response, a prognostic indicator, and an immune therapy target.…”
Section: Kcnq1ot1 In Human Cancersmentioning
confidence: 99%
“…A previous report indicated that KCNQ1OT1 was associated with cell proliferation, apoptosis, prognosis, invasion, and metastasis in various cancers [ 10 , 42 44 ]. Further, KCNQ1OT1 facilitated invasion and inhibited apoptosis in oral squamous cell carcinoma by regulating the miR-185-5p/Rab14 axis [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, KCNQ1OT1 significantly increases migration and invasion in hepatocellular carcinomas and osteosarcomas [143,144]. In small cell lung cancer, the inhibition of KCNQ1OT1 induces apoptosis and sensitizes cells to etoposide by interrupting JAK/STAT signaling [145]. Additionally, KCNQ1OT1 expression is upmodulated in methotrexate-resistant colorectal cancer cells, and KCNQ1OT1 silencing re-sensitizes resistant cells to methotrexate through downregulating cAMP-response element binding protein (CREB) and CREB-binding protein (CBP) levels [146].…”
Section: Linc02418mentioning
confidence: 99%